Optimalisasi Pemasaran Digital dan Estetika Bisnis UMKM : Studi Kasus Pengembangan Kebaya'e Dewe di Pasar Triwindu Surakarta - Destina Paningrum; Sendyka Duwi Firnando Putra; Farah Adiba; Talitha Sahda Hanifah; Dinda Kurniawan (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service aims to increase the digital marketing capacity and business aesthetics of Kebaya'e Dewe Micro, Small and Medium Enterprises (MSMEs) which operate in the field of traditional clothing, especially kebayas at Triwindu Market, Surakarta. The main problem faced by partners is the limited use of digital media as a promotional tool and less than optimal product packaging and visualization. The solutions offered include digital marketing training via social media Instagram and Tik-Tok, creating attractive visual content, redesigning product packaging, and rejuvenating physical stores to make them more aesthetic and in line with the current target market. The results of the activity show an increase in partners' understanding of digital marketing strategies, an increase in the quality of shop displays, and an increase in consumer interest in traditional kebaya products. This activity has a positive impact on the professionalism and competitiveness of local MSMEs.